PENERAPAN PRAKTIKUM KIMIA BERMUATAN LIFE SKILLS SEBAGAI UPAYA MEMPERSIAPKAN CALON GURU YANG BERKARAKTER - Endang Widjajanti (LPMPP Universitas Negeri Yogyakarta, 2010)
Abstract: Character Education for Chemistry Students Through PracticumsLaden with Life-Skills. This study aims to build chemistry students charactersthrough Physical Chemistry I and II practicums laden with life skills. This actionresearch study consisted of four steps, i.e. planning, action, observation andreflection and involved students joining Physical Chemistry I and II laboratorywork. The study focused on psychomotor and affective aspects. The instrumentswere observation sheets and questionnaires. The data were analyzed using thequalitative descriptive technique. The results show that Physical Chemistry I and IIlaboratory work activities laden with life skills can build students characters. Theycan develop such characters as discipline, responsibility, obedience, thoroughness,thriftiness, truthfulness, gentleness, tolerance, initiative, creativeness, and wisdom.Keywords: life skills, character building